Patients with longstanding primary antiphospholipid syndrome: retrospective analysis of organ damage and mortality. (October 2014) - Dall'Ara, F; Reggia, R; Taraborelli, M; Andreoli, L; Taglietti, M; Frassi, M; Franceschini, F; Tincani, A
Objective: To assess the prevalence of disease- and therapy-related complications and of the organ damage after a follow-up of 15 years or more in patients with primary antiphospholipid syndrome (PAPS). Methods: Medical records of patients prospectively followed in our centre for at least 15 years were retrospectively reviewed. Results: Thirty-five Caucasian patients (33 female, two male) with diagnosis of PAPS followed from 1984 to 2013 with a mean age at onset of 32 years (SD 8.17) and a median follow-up of 20.5 years (range 15–30) were included. The occurrence of systemic autoimmune disease was observed in 14% of patients. Haemorrhagic, infective and neoplastic events were recorded in 34%, 6% and 9% respectively. Organ damage was present in 20% of patients at the end of the follow-up (17% neurological and 3% renal) and was significantly associated with the occurrence of thrombotic events ( p : 0.027), particularly arterial ( p < 0.001). A 48-year-old patient died from sepsis. Conclusion: During long-term follow-up of PAPS systemic autoimmunity is not unexpected. Organ damage progresses in a significant proportion of patients especially if they have suffered previous arterial events. Our study clearly shows the possible evolution of the disease and of organ damage, suggesting that optimal therapy and optimal prophylaxis of each PAPS patient should be carefully identified and strictly applied.